A coherent-averaged dual-comb spectrometer based on environment-shared fiber lasers and digital error correction. (December 2022) - Yu, Haoyang; Li, Yu; Ma, Qiuying; Zhou, Qian; Li, Xinghui; Ren, Wei; Ni, Kai
Highlights: A coherent-averaged dual-comb spectrometer based on environment-shared fiber lasers is first demonstrated. Environment-sharing enables long-term aliasing-free dual-comb interferograms in several hours. Digital error correction is utilized to recover full mutual coherence and realize long-term coherent averaging. The transmittance spectra of H 13 CN and C2 H2 gases with high resolution and high signal-to-noise ratio are obtained. Abstract: Dual-comb spectroscopy (DCS) has been an emerging spectrometric technique with high resolution, high sensitivity, broad spectral range and fast acquisition speed. However, it is hard to achieve high long-term stability and high mutual coherence with low system complexity, which hinders the widespread usage in field-deployed applications. In this paper, we demonstrate a simplified free-running dual-comb spectrometer with long-term stability and mode-resolved resolution. Two free-running mode-locked fiber lasers are environment-shared to achieve effective common-mode noise suppression, which enables long-term aliasing-free dual-comb interferograms (IGMs). Post-proposing error correction algorithm is then utilized to recover full mutual coherence and realize coherent averaging. As a result, the transmittance spectra of H 13 CN and C2 H2 gases with high resolution and high signal-to-noise ratio (SNR) can be measured. To the best knowledge of us, this is the first demonstration of coherent-averaged DCS based on environment-shared free-running fiber lasers, which is promising for promoting the dual-comb spectrometer out of the laboratory and realizing field-deployed applications.